Extracorporeal Membrane Oxygenation Support After Heart Transplantation in Children—Outcomes of a Single Center Cohort. Issue 4 (April 2020) - Nair, Asha G.; Sleeper, Lynn A.; Smoot, Leslie B.; Wigmore, Daniel; Mecklosky, Jessica; Andren, Kristofer; Bastardi, Heather J.; Blume, Elizabeth D.; Fynn-Thompson, Francis; Thiagarajan, Ravi R.; Alexander, Peta M. A.
Abstract : Objectives: Extracorporeal membrane oxygenation is used for postcardiotomy low cardiac output but is less established following heart transplantation. We characterized outcomes for children supported with extracorporeal membrane oxygenation after heart transplantation. Design: Single-center retrospective study. Setting: Large pediatric cardiac referral center. Patients: All patients who received heart transplantation and were cannulated to extracorporeal membrane oxygenation between 1995 and 2016. Interventions: Primary outcome measure was mortality 12 months postextracorporeal membrane oxygenation. Patient characteristics were analyzed for association with outcome according to early graft failure (extracorporeal membrane oxygenation ⩽ 7 d after heart transplantation), or late graft failure. Measurements and Main Results: There were 246 heart transplants during the study period and 50 extracorporeal membrane oxygenation runs in 44 patients. Median time from transplant to extracorporeal membrane oxygenation was 1 day (range, 0–11.7 yr), with early graft failure in 28 patients (median 1, range 0–2 d) and 22 extracorporeal membrane oxygenation runs in 20 late graft failure patients (median, 0.8 yr; range, 8 d to 11.7 yr), including four patients with prior extracorporeal membrane oxygenation for early graft failure. Twenty-six patients (59%) survived to hospital discharge, and survival 12 months postextracorporeal membrane oxygenation was 24 patients (55%), lower in those with late graft failure (40% vs 67%; p 0.02). Independent risk factors for 12-month mortality were congenital heart disease, higher pulmonary vascular resistance indexed to body surface area (> 2.2 Woods U/m 2 ), and higher creatinine. Higher panel reactive antibody levels were associated with 12-month mortality in the late graft failure group only. Conclusions: Extracorporeal membrane oxygenation can be effectively used to rescue patients with graft dysfunction after heart transplantation but is associated with high early mortality. Factors associated with mortality within 12 months include presence of congenital heart disease, renal dysfunction, elevated pulmonary vascular resistance indexed to body surface area and in those supported with extracorporeal membrane oxygenation late after heart transplantation, significant human leukocyte antigen sensitization.